Selective laser melting of stainless steel 316L with low porosity and high build rates - Sun, Zhongji (2016)
The present study employs fast scanning speeds to fabricate high-density stainless steel 316L (SS316L) parts via selective laser melting (SLM). It aims to improve the production rate while maintaining a low porosity for the SLM-built parts. Density values of > 99% were recorded for all the fabricated samples in this study. The scanning speed of the laser could be much improved due to the use of 380 W power laser. The overall build rate in this study is supposed to be enhanced by ~ 72% as compared to commonly used processing parameters. Detailed microstructural characterization was carried out in order to obtain an in-depth understanding of the microstructure of SLM-built SS316L. The microhardness of built parts is between 213 and 220 HV, which is much higher than that of the standard annealed counterpart of ~ 155 HV. This study provides an insight on how to improve SLM build rates without any loss of parts' density and mechanical properties.